THE USE OF ENGLISH LANGUAGE TEACHING PODCAST IN TEACHING LISTENING OF STUDENTS - Sangkala, Ismail; ul Haq, Muhammad Zia; Sakka, Fitriah Binti (JKIP (Jurnal Keguruan dan Ilmu Pendidikan), 2015)
This research is descriptive method, it aimed to give description about the effectiveness of ELT Podcast in encouraging the students’ motivation in learning listening skill at Students’ of Class XI MA GUPPI Samata, Gowa. The treatment in this research was giving ELT Podcast focus to dialog material for six meeting. After that, the researcher used the questionnaire to collect the data of sample to determine the motivation of students in studying listening. The instrument was questionnaire, it used to get the students’ motivation in learning listening through ELT podcast. The questionnaire consisted of 20 items and they were divided into two statements; they are 15 positive statements and 5 negative statements. After doing the research, the researcher found that the students had a high motivation in learning listening by using ELT Podcast at Students’ of Class XI MA GUPPI Samata, Gowa. This statement was proved by the finding of the data through using a questionnaire that showed the students’ response was dominated by strongly agreed and agree there were 15 students (51.72%) chose high motivation, 14 students (48.28%) chose very high motivation and the mean score of questionnaire is 79. Based on these data, the researcher concluded that ELT Podcast is a good media that should be considered to be applied in the English classroom, because it showed a good interest on the students in learning listening.